Polyphenols and Novel Insights Into Post-kidney Transplant Complications and Cardiovascular Disease: A Narrative Review - Bustos, Nicolas I.; Sotomayor, Camilo G.; Pol, Robert A.; Navis, Gerjan J.; Bakker, Stephan J. L. (Frontiers in Cardiovascular Medicine, 2021)
Kidney transplantation is the preferred treatment for end-stage kidney disease. It is, however, not devoid of complications. Delayed graft function related to ischemia-reperfusion injury (IRI), calcineurin inhibitor (CNI) nephrotoxicity, diabetes, and a particularly high-rate cardiovascular disease (CVD) risk, represent important complications following kidney transplantation. Oxidative stress and chronic low-grade inflammation are mechanisms of disease incompletely abrogated in stable kidney transplant recipient (KTR), contributing to the occurrence of these complications. Polyphenols, bioactive compounds with recognized antioxidant and anti-inflammatory properties have been strongly associated with prevention of CVD in the general population and have been shown to decrease IRI and antagonize CNI nephrotoxicity in animal experimental models, therefore they may have a role in prevention of complications in KTR. This narrative review aims to summarize and discuss current evidence on different polyphenols for prevention of complications, particularly prevention of CVD in KTR, pointing toward the need of further studies with potential clinical impact.